Why Don't the Poor Save More? Evidence from Health Savings Experiments - Dupas, Pascaline; Robinson, Jonathan (American Economic Review, 2013)
Using data from a field experiment in Kenya, we document that providing individuals with simple informal savings technologies can substantially increase investment in preventative health and reduce vulnerability to health shocks. Simply providing a safe place to keep money was sufficient to increase health savings by 66 percent. Adding an earmarking feature was only helpful when funds were put toward emergencies, or for individuals that are frequently taxed by friends and relatives. Group-based savings and credit schemes had very large effects.